Inferior mesenteric artery arteriovenous malformation, a rare cause of ischemic colitis: A case report. Issue 12 (24th March 2023) - Chang, Ching-Tang; Lim, Wei-Xiong; Liu, Ting-Ting; Lin, Yueh-Ming; Chang, Ching-Di
Abstract : Rationale: An arteriovenous malformation (AVM) is an abnormal tangle of blood vessels that connects the arteries and the veins. Because normal capillary bed is partially or completely absented in the AVM, the blood passes quickly from the arteries to the veins, which disrupts normal blood flow and oxygen supply to the surrounding tissues. This is called "steal phenomenon, " and in the inferior mesenteric artery (IMA) territory, this may lead to abdominal pain, gastrointestinal bleeding, portal hypertension, and even ischemic colitis. Patient concerns: A 67-year-old man presented to our emergency department because of left side abdominal pain. Diagnoses: The abdominal computed tomography with contrast enhancement revealed a cluster of abnormal vascular lesions abutting the IMA with early opacification of the left colonic marginal vein. In addition, poor enhancement of segmental colonic wall was found from proximal descending colon to middle rectum. The diagnosis of AVM of the IMA and ischemic colitis was made. Interventions: The patient underwent left hemicolectomy as well as the AVM resection. Outcomes: He was discharged uneventfully after the surgery without complications. Lessons: IMA AVM carries the risk of ischemic colitis. computed tomography scan is helpful not only to the diagnosis of AVMs but also to exclude other lesions as well. Treatment options include endovascular embolization, surgical intervention, and a combination of both. Due to the complexity of this disease, treatment requires a case-specific multidisciplinary approach and a coordination of medical, radiological, and surgical staffs.